A Literature Review: on the Implementation of the 5S Leadership Model to Improve the Quality of Nursing Care Documentation - Julaiha Julaiha; Iskim Luthfa; Dyah Wiji Puspita Sari; Iwan Ardian (GLOBAL HEALTH SCIENCE GROUP, 2026)
The Quality and Safety Education for Nurses (QSEN) program is an educational initiative designed to equip nurses with the knowledge, skills, and attitudes necessary to continuously improve quality and patient safety within healthcare systems. Junior nurses, as frontline providers of nursing care, require adequate competencies in patient safety aspects. This study aims to identify and synthesize scientific findings regarding the effectiveness of the QSEN program in improving the knowledge, skills, and attitudes of junior nurses. This study employed a Systematic Literature Review following the PRISMA guidelines. Articles published between 2021 and 2026 were retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar. The initial search identified 3,500 records. After removing 1,150 duplicates, 1,900 records were screened. A total of 1,600 records were excluded based on title and abstract. Of the remaining 300 articles, 120 could not be retrieved. Subsequently, 180 full-text articles were assessed for eligibility, and 158 were excluded due to not meeting inclusion criteria. Finally, 22 studies were included in the synthesis. The findings indicate that the implementation of the QSEN program has a positive impact on improving junior nurses’ knowledge of patient safety (60–85%), enhancing clinical skills (55–80%), and improving professional attitudes in nursing practice (70–90%). Several factors such as organizational support, effective leadership, clinical supervision, and continuous training play a crucial role in the successful implementation of the QSEN program. The QSEN program is effective in improving the knowledge, skills, and attitudes of junior nurses. The success of its implementation is strongly influenced by organizational support, leadership, and an adequate supervision system.